Fluktuasi Biaya Haji Dalam Rupiah, Dolar AS dan Dinar: Perspektif Investasi Syariah - Arina Hidayati (Muslim Heritage, 2018)
Abstract: Haji fee always fluctuated from time to time due to changes in economic conditions. The study compared fluctuations Haji Cost of Year 1998-2017 in the currency Rupiah, US Dollar and Gold Dinar to determine the stability of Hajj Cost fluctuations from year to year as consideration of financial planning in preparation for Hajj and other long-term needs as a form of investment sharia. The research method in this study is qualitative descriptive method. Data collected from the Presidential on Fees Hajj of the Year 1998-2017, the data exchange in the BI and the price of the dinar in geraidinar.com then process the data in the form of a non descriptive statistics. From the discussion of research on the fluctuation of the Year 1998-2017 Haji fee in Rupiah, US Dollar and the Dinar result that the US dollar is more stable than the amount, is more stable than Rupiah Dinar and Dinar value and purchasing power of the most volatile than Rupiah and US Dollar. Dinar most encouraged to be the choice of savings in preparing for Hajj fees and other long-term funding needs, poor second to the US Dollar and Rupiah ranked third. Islamic investment safest long term is in dinars, as it has a value and purchasing power of the most stable, followed by the US dollar and the rupiah is recommended only used in everyday financial transactions in the short term.Abstrak: Biaya Haji senantiasa mengalami fluktuasi dari waktu ke waktu seiring dengan perubahan kondisi perekonomian. Penelitian ini membandingkan fluktuasi Biaya Haji dari Tahun 1998-2017 dalam satuan mata uang Rupiah, Dolar AS dan Dinar Emas untuk mengetahui stabilitas fluktuasi Biaya Haji dari tahun ke tahun sebagai bahan pertimbangan perencanaan keuangan dalam rangka persiapan Ibadah Haji dan kebutuhan jangka panjang lainnya sebagai bentuk investasi syariah. Metode penelitian dalam penelitian ini bersifat kualitatif dengan metode deskriptif. Data dikumpulkan dari Kepres tentang Biaya Haji dari Tahun 1998-2017, data nilai tukar mata uang di BI dan harga dinar di geraidinar.com kemudian mengolah data dalam bentuk non statistik deskriptif. Dari pembahasan penelitian terhadap fluktuasi Biaya Haji dari Tahun 1998-2017 dalam Rupiah, Dolar AS dan Dinar diperoleh hasil bahwa Dolar AS lebih stabil daripada Rupiah, Dinar lebih stabil daripada Rupiah dan Dinar memiliki nilai dan daya beli paling stabil daripada Rupiah dan Dolar AS. Dinar paling dianjurkan menjadi pilihan tabungan dalam mempersiapkan Biaya Haji dan kebutuhan dana jangka panjang lainnya, urutan ke dua Dolar AS dan Rupiah diurutan ketiga. Investasi syariah jangka panjang paling aman adalah dalam Dinar, karena memiliki nilai dan daya beli paling stabil, disusul Dolar AS dan Rupiah dianjurkan hanya digunakan dalam transaksi keuangan sehari-hari dalam jangka pendek.